1995
DOI: 10.1093/nar/23.6.1036
|View full text |Cite
|
Sign up to set email alerts
|

A modified single-strand annealing model best explains the joining of DNA double-strand breaks in mammalian cells and cell extracts

Abstract: The joining of DNA double-strand breaks in vivo is frequently accompanied by the loss of a few nucleotides at the junction between the interacting partners. In vitro systems mimic this loss and, on detailed analysis, have suggested two models for the mechanism of end-joining. One invokes the use of extensive homologous side-by-side alignment of the partners prior to joining, while the other proposes the use of small regions of homology located at or near the terminus of the interacting molecules. to discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…In plants, three different approaches unambiguously demonstrated that extrachromosomal recombination proceeds efficiently by SSA (Puchta and Hohn, 1991;Bilang et al, 1992;De Groot et al, 1992; for review, see Puchta and Meyer, 1994). Interestingly, a similar mechanism is used for NHEJ: the majority of junctions contain small patches of homologous nucleotides between reaction partners, which is best explained by the operation of a "SSA-like" mechanism (Lehman et al, 1994;Nicolas et al, 1995;Mason et al, 1996;Gorbunova and Levy, 1997;Salomon and Puchta, 1998; for review, see Gorbunova and Levy, 1999). Thus, SSA and SSA-like mechanisms might be the most prominent mode for the rejoining of broken DNA molecules in higher eukaryotes.…”
Section: Efficient Repair Of Genomic Dsbs By Single-strand Annealing mentioning
confidence: 99%
“…In plants, three different approaches unambiguously demonstrated that extrachromosomal recombination proceeds efficiently by SSA (Puchta and Hohn, 1991;Bilang et al, 1992;De Groot et al, 1992; for review, see Puchta and Meyer, 1994). Interestingly, a similar mechanism is used for NHEJ: the majority of junctions contain small patches of homologous nucleotides between reaction partners, which is best explained by the operation of a "SSA-like" mechanism (Lehman et al, 1994;Nicolas et al, 1995;Mason et al, 1996;Gorbunova and Levy, 1997;Salomon and Puchta, 1998; for review, see Gorbunova and Levy, 1999). Thus, SSA and SSA-like mechanisms might be the most prominent mode for the rejoining of broken DNA molecules in higher eukaryotes.…”
Section: Efficient Repair Of Genomic Dsbs By Single-strand Annealing mentioning
confidence: 99%
“…In addition to that, SSA may well occur at very short homology patches of only a few nucleotides. This nonhomologous variant of the SSA mechanism represents another pathway for the direct rejoining of double-strand breaks in DNA and leads to the deletion of terminal sequences (Roth et al 1985;Thacker et al 1992;Lehman et al 1994;Nicolás et al 1995). A very efficient SSA-recombination machinery has been previously shown to exist in Xenopus oocytes (Maryon & Carroll 1989, 1991a and eggs (Lehman et al 1993) which is absolutely dependent on a 5 0 -3 0 -exonuclease activity.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms are likely to involve exonucleolytic resection of DSB-termini to generate long single-stranded tails that expose small fortuitious patches of sequence homology at which single-strand annealing may occur. Processing of these partially paired structures yields junctions of the deletion type Lehman et al 1994;Nicolás et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Simple ligation will result in junctions with no homology. Short stretches of homology may be a result of SSA-like mechanisms [13], while longer stretches might be from an SDSA copying of ectopic chromosomal DNA into the break [14].…”
Section: Non-homologous End-joining Recombinationmentioning
confidence: 99%